Determinación de la respuesta agronómica de 10 accesiones de cebada (Hordeum vulgare. L) dísticas y peladas en el segundo año de evaluación, en la zona agroecológica de Laguacoto III, cantón Guaranda - Gavilanez Vasconez, Jennifer Dayana (2024)
This research was carried out in the agroecological zone of Laguacoto III, with the following objectives: I) To identify the main agronomic and sanitary characteristics in the cultivation of barley, peeled type, II) To select the best agronomic response materials for the agroecological zone under study, III) To establish the main agronomic and sanitary characteristics in the cultivation of barley, distich type. A randomized complete block design (RCBD) was used, with 10 accessions of barley, distich and peeled, in 3 replications; an analysis of variance, Tukey's test at 5%, correlation analysis and simple regression were carried out. Variability was evidenced in the morphological components of the distich barley accessions, 80% of the accessions presented an erect growth habit, and the remaining 20% had an intermediate growth habit. Sixty % of the distic barley accessions in the straw type descriptor were strong stemmed, and the other 40 % showed an intermediate stem. Of the 5 peeled barley accessions, 80 % showed good plant vigor and the remaining 20 % showed fair plant vigor. In the growth habit descriptor, 60 % showed an erect habit and 40 % showed an intermediate habit. The best yields obtained from the distich barley accessions were: T1 (CD-19-001) with 2024.7 kg/ha, and T3 (CD-19-004) with 2159.9 kg/ha, while T4 (CD-19-013) with 1706.1 kg/ha was the one with the lowest average yield. For peeled barley accessions the best average yield was recorded in T2 (CD-19-006) with 3824.9 kg/ha, similarly the lowest yield was evidenced in accession T4 (CD-19-011), with 2751.1 kg/ha The agronomic variables that reduced the yield of distic and peeled barley were especially Plant height, hectoliter weight and 1000-grain weight. The 10 accessions of distich and peeled barley showed a moderately resistant reaction (MR) to the incidence and severity of foliar diseases, such as; Yellow rust (Puccinia striiformis), Leaf rust (Puccinia hordei), Virus, Fusarium